Strengthening social enterprises for inclusive growth: Philippines - Marife Magno-Ballesteros; Gilberto M. Llanto (Philippine Institute for Development Studies (PIDS), 2017)
Social enterprises are gaining popularity in many parts of the world due to their great potential to advance the agenda of inclusive and sustainable growth. The uniqueness of social enterprises lies on their core advocacies, i.e., the attainment of community well-being and human development. Their main difference to traditional micro, small, and medium enterprises is that they have a hybrid nature wherein they adopt business solutions to social problems. The Philippines, in particular, has a social and cultural environment that is conducive to the framework of social entrepreneurship given that the country has had a widespread focus on bottom-of-the-pyramid issues and on the movement toward the stronger participation of the civil society and the private sector in social issues. However, the current policy environment in the country is still unresponsive to the growth of social enterprises. Social enterprises are currently viewed as traditional micro, small, and medium enterprises despite the differences. The government should give additional support to social enterprises by providing incentives for mixed financing; improving the suitability of the environment for grants, international aid and venture capitalists; and recognizing the social enterprises' longer incubation period.
Keywords: 330; social enterprises; community economies; inclusive growth; social and solidarity economy